Dietary sodium restriction for mild hypertension in general practice. Issue 6363 (5th February 1983) - Watt, G C; Edwards, C; Hart, J T; Hart, M; Walton, P; Foy, C J
Abstract : Eighteen patients with stable mild hypertension (mean blood pressure 144/93 mm Hg) restricted their sodium intake for eight weeks while taking part in a double blind randomised crossover trial of slow sodium and placebo tablets. Mean 24 hour urinary sodium excretion was 143 mmol(mEq) during the period on slow sodium and 87 mmol during the period on placebo. Five patients were unable to reduce their sodium intake below 120 mmol, but the others had a mean 24 hour urinary sodium excretion of 59 mmol during the period on placebo. There was no significant difference in blood pressure between the slow sodium and placebo treatment periods, although the study had a power of 99% to detect a difference of 5 mm Hg in mean arterial pressure between the two periods. Moderate dietary sodium restriction does not lower blood pressure in patients with this degree of hypertension.